Cooking the Australian way : revised and expanded to include new low-fat and vegetarian recipes - Germaine, Elizabeth; Burckhardt, Ann, 1933- (Minneapolis, MN : Lerner Publications, 2004)
An introduction to the cooking of Australia, featuring such recipes as egg and bacon pie, Anzac biscuits, pumpkin soup, and glazed kiwi tart. Also includes information on the history, geography, customs and people of the "land down under."
Includes index.
6.2
5-8
Keywords: Australian cooking; Australia -- Social life and customs